CAN MOTIVATION AFFECT THE APPLICATION OF TOKEN AREND TIME TO AKHLAQ AQIDAH LEARNING IN MADRASAH IBTIDAIYAH? (International Conference on Social and Islamic Studies, 2021)
The formation of praiseworthy morals becomes a necessity in the education process in Madrasah Ibtidaiyah, so that the process of learning moral aqidah material must always apply innovative and creative learning. So, the purpose of this study looked at the relationship between the applications of the arend time token learning model on moral aqidah material in Madrasah Ibtidaiyah (MI). Not to forget this study will also look at whether student learning motivation has a significant impact on learning models and improved student learning outcomes at MI. To achieve the purpose of the study, experiments with an ANAVA analysis were used two ways. This study sample was as many as 104 learners spread across class V MI KKM Kapongan Situbondo Sub district. Data collection techniques for learning outcomes from students' objective test results, while for measuring motivation using questionnaires. There are four research findings that can be explained, namely; 1. There is a difference between students who follow the time token arend learning model and the conventional learning model; 2. There is aninteraction between learning models and motivation aimed at student learning outcomes; 3. For students with high motivation, there is a difference between the application of the time token arend learning model and the conventional learning model; 4. For students with low motivation, there are differences in the learning model of time token arend with conventional. Then overall describing the time token arend can be applied to moral aqidah learning materials to improve student learning outcomes in MI. Then motivation is needed so that students at MI can follow the arend time token learning model effectively.